Distal radius fractures: surgical treatment with internal fixation - Valentini, Roberto; De Fabrizio, Giovanni; Piovan, Gianluca; Bolcic, Stefano; Bernobi, Sergio; Fancellu, Giovanni (Acta Biomedica Atenei Parmensis, 2014)
Aim of the study: to evaluate the efficacy of plates and screws with angular stability in osteosynthesis of fractures of the distal radius. Materials and methods: we analyzed 52 patients undergone surgery for fracture of the distal radius at the Clinica Ortopedica dell’Università di Trieste; in half of the patients osteosynthesis was provided using Synthes’ LCP plates, in the other half we utilized a multidirectional and angular stable plate (“Aptus Radius” by Medartis). Mean follow-up was 28 ± 10 months, patients were evaluated with DASH score (disability of arm shoulder and hand) and the modified Gartland Werley score. Results: there were no significant differences between the two groups in terms of joint function, motility, volar and radial mean inclination. Conclusions: based on clinical and radiological results using angular stability plates must be considered as the method of election in the treatment of fractures of the distal epiphysis of the radius; in particular, thanks to the broader technical capabilities that they allow, are particularly indicated in unstable fractures.